Soočanje mladostnika s kronično ledvično boleznijo - Kreft, Ivana (Medicinski razgledi, 2009)
Adolescence is a developmental stage in which a person is learning to master cognitive, emotional, social and moral maturity. Adolescents growing up with chronic renal disease enter this stage later and it usually takes them longer to reach the next developmental stage of early adulthood. The reason for this is probably the disease, which brings additional challenges to their lives andto the achievement of autonomy. However, there are factors which have a positive influence on the process of adapting to the disease, such as early preparation for treatment and an encouraging family environment. This is why psychosocial interventions focus on achieving successful adaptation to the disease with the aim ofhelping adolescents and their families continue their everyday life with minimum impact of treatment, i. e. to achieve their best stage of functioning.
Keywords: Adolescenca; Kidney Failure, Chronic; Psychology; Ledvica, odpoved kronična; Social Support; Socialna pomoč; kronična ledvična odpoved; Adolescence; mladostniki; soočanje; psihosocialna pomoč